Combined analysis of metabolomics and transcriptomics reveals the effects of sugar treatment on postharvest strawberry fruit quality - Zihui Zhang; Riru Tian; Junyi Wan; Yan Wang; He Li (BMC Plant Biology)
Abstract The composition and accumulation of soluble sugars are key factors influencing the development of fruit flavor, and although the application of fertilizers can increase the postharvest fruit quality, long-term application will cause certain food hazards. Therefore, evaluating the effects of externally applied sugar sources on fruit quality is essential for improving postharvest strawberry quality. In this study, exogenous sugar application significantly enhanced the postharvest quality of ‘Yanli’. Specifically, strawberries treated with 0.2 mol∙L−1 fructose increased the single fruit weight, soluble solids content and soluble sugar content. Based on these results, combined metabolomic and transcriptomic analyses were performed to assess the impact of 0.2 mol∙L−1 fructose treatment. The results showed that broadly targeted metabolomics screened a total of 371 significantly different metabolites, 123 up-regulated and 248 down-regulated. Sugar-targeted metabolomics further revealed a marked increase in fructose content to 43.40 mg∙g−1. Transcriptomic analysis identified 3,506 differentially expressed genes. Integration of transcriptomic and metabolomic data indicated that FaINV and FaSUS are key genes involved in the sugar metabolism pathway. These findings elucidate molecular responses to exogenous sugar treatment and offer a foundation for further investigation of gene functions in postharvest fruit quality regulation.